Análisis de la gestión de stock en el Instituto de Investigaciones de la Amazonía Peruana, Iquitos - año 2023 - Melendez Flores, Armando Junior (2024)
The present research study entitled "Analysis of Stock Management at the Research Institute of the Peruvian Amazon Iquitos year 2023", was developed with the objective of determining the level of stock management at the Research Institute of the Peruvian Amazon Iquitos year 2023, so it was determined to carry out a descriptive research, with a non-experimental design, for which there was a study population of 22 workers from the Institution who voluntarily decided to participate in this research work, and were These were the ones who answered the questions of the questionnaire designed for this purpose; Having carried out the analysis of the responses, it was determined that 65.4% of the workers have a medium level of financial knowledge and 86% of the workers have a medium level of stock management and 56.3% also have a level means of management for the control of stock distribution, it was concluded that stock management at the Peruvian Amazon Research Institute is of a medium level.